2021
DOI: 10.1016/j.omtn.2021.08.007
|View full text |Cite
|
Sign up to set email alerts
|

A synonymous mutation in IGF-1 impacts the transcription and translation process of gene expression

Abstract: Insulin-like growth factor 1 (IGF-1) is considered to be a crucial gene in the animal development of bone and body size. In this study, a unique synonymous mutation (c.258 A > G) of the IGF-1 gene was modified with an adenine base editor to observe the growth and developmental situation of mutant mice. Significant expression differences and molecular mechanisms among vectors with different alanine synonymous codons were explored. Although modification of a single synonymous codon rarely interferes with animal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 83 publications
0
11
0
Order By: Relevance
“…Missense variants are known to alter the amino acid sequence, and have been shown to impact the interacting DNA-transcription factors, resulting in changed expression of other genes [87]. Low-impact variants including synonymous variants have also been shown to influence gene expression by disrupting transcription and splicing, as well as mRNA stability [8891].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Missense variants are known to alter the amino acid sequence, and have been shown to impact the interacting DNA-transcription factors, resulting in changed expression of other genes [87]. Low-impact variants including synonymous variants have also been shown to influence gene expression by disrupting transcription and splicing, as well as mRNA stability [8891].…”
Section: Discussionmentioning
confidence: 99%
“…Missense variants are known to alter the amino acid sequence, and have been shown to impact the interacting DNA-transcription factors, resulting in changed expression of other genes [87]. Low-impact variants including synonymous variants have also been shown to influence gene expression by disrupting transcription and splicing, as well as mRNA stability [88][89][90][91]. High-impact variants consisted of two downregulated splice acceptor variants, two upregulated start-lost variants, and the upregulation of most stop-gained variants (electronic supplementary material, figure S2).…”
Section: (B) Impact Of Different Classes Of Mutations On Gene Expressionmentioning
confidence: 99%
“…Since this mutation did not involve alteration of the encoded protein, the specific mode of its effect requires further investigation. Despite the long-standing neutral function of synonymous mutations, studies in recent years have demonstrated that synonymous mutations affect the efficiency and stability of transcription and translation of genes [ 40 , 41 , 42 ]. PmGrx2 -E3398 could be developed as a molecular marker for breeding shrimp tolerant to stress.…”
Section: Discussionmentioning
confidence: 99%
“…Missense variants are known to alter the amino acid sequence, and have been shown to impact the interacting DNA-transcription factors, resulting in changed expression of other genes (Ding et al 2015). Low-impact variants including synonymous variants have also been shown to influence gene expression by disrupting transcription and splicing, as well as mRNA stability (Pagani et al 2005, Presnyak et al 2015, Stergachis et al 2013, Wang et al 2021.…”
Section: Impact Of Different Classes Of Mutations On Gene Expressionmentioning
confidence: 99%